Knowledge and practice of nursing professionals about prophylaxis of ophthalmia neonatorum - Fernanda Carla Pereira Duarte; Fernanda Garcia Bezerra Góes; Juliana Rezende Montenegro Medeiros de Moraes; Laura Johanson da Silva; Liliane Faria da Silva; Maria da Anunciação Silva (Universidade Federal do Rio de Janeiro, 2019)
Abstract Objective: To analyze the knowledge and practice of nursing professionals about the prophylaxis of ophthalmia neonatorum. Method: Descriptive study, of qualitative approach, carried out in the first semester of 2018, in a city hall hospital located in the lake area of the Rio de Janeiro's state, through semi-structured interviews with 14 Nursing professionals participating in the care of the newborn, whose data were submitted to the Thematic Analysis. Results: From the three emerging thematic categories, there are gaps in knowledge related to ophthalmia neonatorum, silver nitrate and the instillation procedure of this prophylactic solution, as well as differences in care practice regarding care before, during and after the procedure. Conclusion and implications for practice: The data point to the importance of training the Nursing team in the prophylaxis of ophthalmia neonatorum, the revision of guidelines and procedures aimed at standardizing the procedure, as well as emphasizing the need for adequate follow-up of pregnant women in prenatal care.